The practice of risk management : implementing processes for managing firmwide market risk - Goldman, Sachs & Co.; SBC Warburg Dillon Read. (London : Euromoney, 1998)
The book is designed to be accessible to both the technical and the non technical reader and allows selective reading without detracting from the overall message.
gau 05/08/16
Loans
Keywords: Risk management; Financial institutions